THE EFFECT OF CARROT JUICE ON REDUCING DYSMENORRHEA PAIN SCALE IN ADOLESCENT GIRLS AT NGORO PUBLIC HEALTH CENTER - Lukita Sari, Cindy Elisa; Sumini, Gempi Tri; Sarmin, Sukati (Jurnal Medika Cendikia, 2024)
Adolescence is the transition to adulthood between the ages of 10 and 19. One of the biological signs of this stage is early menstruation (menarche). Dysmenorrhea occurs at the onset of menstruation. Uterine pain that happens before or during menstruation is a sign of dysmenorrhea. This discomfort disrupts adolescents' activities, making it difficult for them to concentrate while studying, due to dysmenorrhea. The aim of this study is to determine the effectiveness of carrot juice in reducing the intensity of dysmenorrhea pain in adolescents. The design of this study is a one-group pretest-posttest design. All adolescent girls aged 14-19 years at the Ngoro Adolescent Posyandu in Ngoro District participated in this study. A purposive sampling technique was used in this study, with a sample size of 37 adolescent girls. Observation sheets and facial pain scales were used to measure dysmenorrhea in adolescent girls. The independent variable in this study is carrot juice, and the dependent variable is menstrual pain. The results of the Wilcoxon test showed that 20 adolescent girls (54.1%) experienced less pain before carrot juice therapy, and 22 adolescent girls (59.5%) experienced no pain after carrot juice therapy. On the third day, the P-value = 0.000 < 0.05, indicating that H1 is accepted, meaning that the administration of carrot juice has an effect on the intensity of dysmenorrhea pain in adolescent girls in the working area of the Ngoro Public Health Center, Ngoro District, Jombang Regency.